Fiscal Policy Coordination in the Waemu After the Devaluation - Rosenberg, Christoph (IMF Working Papers; Working Paper ;, 1995)
This paper examines the economic implications of fiscal policy coordination in the West African Economic and Monetary Union (WAEMU) in the light of the January 1994 devaluation of the CFA franc. Diverging tax, tariff, and budgetary politics are identified and it is argued that the resulting fiscal externalities have prevented the zone from reaping the full benefits of a monetary union. The paper shows that the devaluation makes it more desirable than ever to have a closer policy coordination to prevent such detrimental fiscal externalities. Recent efforts in this field are reviewed and evaluated. Finally, the paper offers some recommendations with respect to the optimal design of tax and tariff rate structures, and the choice of budgetary convergence criteria.